Creep feeding supplemented with roughages improve rumen morphology in pre-weaning goat kids - Nay Naing Htoo; Basit Zeshan; Aung Tun Khaing; Than Kyaw; Erkihun Aklilu; Mohd Azam Khan Goriman Khan (Researchers Links, Ltd., 2018)
Boer crossbred goats (n=48) single born kids, seven-day-old (live weight 4.4±0.09kg) were divided into 3 treatment groups, each having 8 females and 8 males. The kids from first treatment group had free access to creep feed with roughage (CFR), second group had free access to creep feed without roughage (CF) while last group (control) had access to their does’ milk (DM) only. All kids had access to their dam’s milk. The kids were weaned at day 84 and two kids from each treatment group were sacrificed. The results showed that the rumen morphological characteristics, papillary surface area and keratinized layer of CFR (4.15mm2, 50.54µm), were not significantly different from CF (3.81mm2, 49.26µm) (P>0.05) but it was significantly different from kids in DM group (1.17mm2, 26.36µm) (P<0.05). The rumen papillary surface area and keratinized layer were also significantly different between CF and DM (P<0.05). The rumen of kids from CFR group had higher sub-mucosa layer thickness (619.8µm), muscle layer thickness (1155.7µm) and rumen wall thickness (1775.4µm) than the rumen of kid in CFR and DM groups (P<0.05). The total surface area of rumen of kids from CFR and CF groups was not significantly different (P>0.05), while total surface area of rumen of both creep fed groups was significantly greater than DM group. The rumen tissue weight of creep-fed kids was 17% greater than those of milk fed kids. Overall, the present study showed that the creep feed supplementation to nursing goat kids improve rumen morphology. Read more at http://researcherslinks.com/current-issues/Creep-Feeding-Supplemented-with-Roughages/20/1/1134/html#lyAKjwLAfprvXT3I.99.